The study of physical and functional characteristics of urban public spaces-a case study of Kota Bahru town, centre Kelantan - Sulaiman, Ahmad Bashri; Shamsuddin, Shuhana; Wan Abdullah, Wan Mohd. Zakry (UTM, 2003)
Cities and towns in Malaysia are fast developing and changing in their effort to meet the current demands of the people that is ever changing. As workplaces, living quality (that is residential settings and recreational facilities) and other environmental condition changes, the towns and cities will evolves into new situation. In the process of change, existing situation will be modified to meet their new uses and frequently it was found that many traces of the existing characteristics are erased. This situation is of great loss to the place where traditional built environment is replaced by a new one that is showing very little sense of continuity from their past situation, depriving the place of its roots and hence their sense of place. Urban public spaces made up the main component of any towns and cities that represent one of the major elements that create its sense of place. It is therefore very important to study and propose or recommend how they could be maintained or adapted for future reference and uses. It is also important to understand the underlying principles of their organisation and design in order to be modified and adapted to be relevant to new and future settlement. The development of towns and cities are normally influenced by many different aspects or characteristics such as physical (either natural or built form), socio-economic factor, land-use pattern, transportation system, psychological, behavioural and many others. They are interdependent (directly or indirectly) which is related to the history and culture of the people living in the town. The study established that the urban pattern in Malaysia is generally based on the pattern of the circulation system and land ownership division. Thus even though existing buildings were rebuilt, generally there were not many changes to the existing pattern except in the built form (that is the grain and texture) that may have experienced some dramatic alteration. Therefore it is important to record and determine the urban pattern as well as the character of the urban spaces of the existing towns and cities for future references.